KIMIA DARAH KUDA LOKAL INDONESIA YANG DIPELIHARA DI DAERAH ISTIMEWA YOGYAKARTA DAN JAWA TENGAH - , RAKA BAYU R ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Blood chemical is used to describe organs functional status in normal physiology condition or in abnormal condtion caused by infectious or non infectious on organs such as : kidney, liver, heart, and muscle. This study was to used the normal average of Serum Glutamic Piruvic Transaminase (SGPT), Serum Glutamic Oxaloacetic Transaminase (SGOT), Blood Urea Nitrogen (BUN), and Indonesian local horse creatinine that is bred in Special District of Yogyakarta and Central Java. This study used 7 Indonesian local horses aged around 2,5 â 6 years old came from Special District of Yogyakarta and Central Java. 5 of them were from Special District of Yogyakarta stable and the other two were from Central Java stable. There were 2 female horses and 5 male horses. 5cc of blood sampling which was taken through jugularis vein kept in a tube no antikoagulan then tested at Klinik Hewan Jogja. The content of SGPT, SGOT, BUN, and creatinine measured by automatic blood analyzer model RT-1940C (Synchron clinical system CX5CE, Beckam USA). The result of this study showed that SGPT range was 9,33-18,09 IU/L, SGOT was 191,58-321,56 IU/L, BUN was 11,87-17,5 mg/dL, and creatinine was 1,23-1,63 mg/dL.